Re-socializing pre-health education in the context of COVID: Pandemic prompts for bio-social approaches - Mitchell-Sparke, Emma; Mitchell, Katharyne Wilcox; Sparke, Matthew Brookman (Frontiers in Medicine, 2022)
COVID-19 has underlined the critical importance of bringing biosocial and biopsychosocial approaches to pre-health education. Given the striking social inequalities that the pandemic has both exposed and exacerbated, we argue that bridging between the biomedical and social sciences with such approaches is now more appropriate and urgently needed than ever. We therefore call for the re-socialization of pre-health education by teaching to develop socio-structural competencies alongside physical and biological science knowledge. We suggest that community partnerships, which address local inequalities and their global interdependencies, should be encouraged as an essential element in all pre-health education. Educators should also support such partnerships as opportunities for students who come from more minoritized and impoverished social backgrounds to see their own social knowledge – including community-based knowledge of health-injustices revealed by the pandemic – as the basis of biopsychosocial expertise. By prioritizing this reconceptualization of pre-health education, we can empower future health workers to prepare more adequately for future health crises in ways that are socially aware and structurally transformative.